A Synthesis and Evaluation of Geosynthetic-Reinforced Base Layers in Flexible Pavements- Part II. Issue 6 (1st January 1997) - Ismeik, M.; Perkins, S.W.
Abstract : In this and a companion paper, studies related to the use of geosynthetics in the base course layer of flexible pavements for the purpose of reinforcement are examined. The purpose of these papers is to provide a synthesis and evaluation of the literature focusing on this application. The companion paper is a review of studies involving physical experiments of reinforced roadways. The majority of the reviewed studies conclude that appreciable improvement can be realized by proper placement of a geosynthetic in the base course of a flexible pavement and that improvement is seen over the entire service life of the pavement and not only for conditions of excessive surface deformation. The companion paper demonstrates that these experimental results taken by themselves are insufficient for the development of an accepted design procedure due to the many dependent variables impacting the problem. It is concluded in the companion paper that the development of a comprehensive analytical model is a necessary step to reach the goal of providing a methodology for the design of such roadways. The purpose of this paper (Part II) is to review existing design techniques developed for this application. Analytical studies using finite element techniques to predict roadway response and to illustrate reinforcement mechanisms are summarized. A brief description of selected on-going research is also included in this paper.